Diversity Strategies and Business Logic: Why Do Companies Employ Ethnic Minorities?. (August 2013) - Ortlieb, Renate; Sieben, Barbara
Firms have many reasons to employ ethnic minorities or refrain from employing them. Management scholars focusing on workplace diversity have made several attempts to describe these reasons, but a theoretically grounded framework is still missing. This article outlines a novel approach to this topic based on resource dependence theory. We propose a typology of diversity strategies defined by the kind of critical resources that ethnic minorities provide to organizations. Focusing on business logic, the typology offers many applications for future research on antecedents and consequences of the strategies, a diverse competence pool, and power relations. We suggest resource dependence theory as a fruitful explanatory approach to diversity and describe practical implications for different actors.